Vascular endothelial cell growth factor receptor 3-mediated activation of lymphatic endothelium is crucial for tumor cell entry and spread via lymphatic vessels - He, Yulong; Rajantie, Iiro; Pajusola, Katri; Jeltsch, Michael; Holopainen, Tanja; Yla-Herttuala, Seppo; Harding, Thomas; Jooss, Karin; Takahashi, Takashi; Alitalo, Kari (Cancer Res, 2005)
Lymphangiogenic growth factors vascular endothelial growth factor (VEGF)-C and VEGF-D have been shown to promote lymphatic metastasis by inducing tumor-associated lymphangiogenesis. In this study, we have investigated how tumor cells gain access into lymphatic vessels and at what stage tumor cells initiate metastasis. We show that VEGF-C produced by tumor cells induced extensive lymphatic sprouting towards the tumor cells as well as dilation of the draining lymphatic vessels, suggesting an active role of lymphatic endothelial cells in lymphatic metastasis. A significant increase in lymphatic vessel growth occurred between 2 and 3 weeks after tumor xenotransplantation, and lymph node metastasis occurred at the same stage. These processes were blocked dose-dependently by inhibition of VEGF receptor 3 (VEGFR-3) signaling by systemic delivery of a soluble VEGFR-3-immunoglobulin (Ig) fusion protein via adenoviral or adeno-associated viral vectors. However, VEGFR-3-Ig did not suppress lymph node metastasis when the treatment was started at a later stage after the tumor cells had already spread out, suggesting that tumor cell entry into lymphatic vessels is a key step during tumor dissemination via the lymphatics. Whereas lymphangiogenesis and lymph node metastasis were significantly inhibited by VEGFR-3-Ig, some tumor cells were still detected in the lymph nodes in some of the treated mice. This indicates that complete blockade of lymphatic metastasis may require the targeting of both tumor lymphangiogenesis and tumor cell invasion.